Helminths of Dermatonotus muelleri (Anura: Microhylidae) from Northeastern Brazil - Alcantara, E. P. [UNESP]; Ferreira-Silva, C. [UNESP]; Silva, L. A. F. [UNESP]; Lins, A. G. S. [UNESP]; Avila, R. W.; Morais, D. H.; Silva, R. J. da [UNESP] (Allen Press Inc, 2018)
The helminth fauna associated with Muller's termite frog, Dermatonotus muelleri, from the southern region of Ceara State, Brazil, was studied. The species richness was 6 helminth taxa, including cystacanths of Acanthocephala and 5 nematode species: Aplectana membranosa, Parapharyngodon silvoi, Raillietnema spectans, larvae of Physaloptera sp., and an unidentified nematode. The overall prevalence was 88.6%, with an average intensity of infection of 123.7 +/- 26.3. The nematode Raillietnema spectans presented the highest prevalence and was the most abundant (d = 0.670). Host body size did not influence the intensity of infection nor the richness of helminth species. This study increases the body of knowledge about the diversity of helminth fauna associated with Dermatonotus muelleri from northeastern Brazil, extending the record of hosts and the geographic distribution of these helminth species.